N-soliton solution for an integrable nonlocal discrete focusing nonlinear Schrödinger equation. (September 2016) - Ma, Li-Yuan; Zhu, Zuo-Nong
Abstract: In this paper, by employing the Hirota's bilinear method, we construct the N -soliton solution for an integrable nonlocal discrete focusing nonlinear Schrödinger (dNLS + ) equation, and give the asymptotic analysis of two-soliton solution. The soliton solutions can be reduced to spatial periodic solution or singular solution by choosing the different parameters. Under continuous limit, the discrete soliton yields the one of nonlocal focusing nonlinear Schrödinger equation.